Alkaline catalyst based on modified nano MgO, and preparation method and application thereof
By modifying the MgO material by monodispersed Ce atoms, a high-activity and stability alkaline catalyst was prepared, which solved the problem of insufficient activity and stability of existing MgO-based catalysts in the reverse water gas transformation reaction, and achieved the following: The effect of efficient catalyzing the conversion of CO2 into CO in carbon dioxide hydrogenation reaction.
Patent Information
- Application Number
- CN202411542298.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing MgO-based catalysts are insufficient in the activity and stability of the reverse water gas conversion reaction, making it difficult to effectively activate and adsorb CO2 gas.
Modify the MgO material by monodispersed Ce atoms to prepare an alkaline catalyst for modifying the MgO material with monodispersed Ce atoms. Specific preparation methods include sol-gas phase binding method and calcination treatment to improve the catalyst Anti-sintering ability and activity.
The modified catalyst exhibits high activity, good selectivity and stability in carbon dioxide hydrogenation reaction, and can effectively catalyze the conversion of CO2 into CO, and is suitable for catalytic processes such as reverse water gas conversion reactions.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure HDA0005113059230000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of rare earth metal additive modified catalysts, and specifically relates to an alkaline catalyst modified by monodispersed Ce atoms on MgO materials, a preparation method and an application thereof, which can effectively regulate the microstructure of MgO to improve the activity and stability of the catalyst, and can be applied to catalytic processes such as reverse water gas shift reaction. Background Art
[0002] The combustion of fossil fuels leads to large amounts of carbon dioxide emissions, which in turn cause greenhouse effects such as global warming. Effectively removing CO2 from the atmosphere is a major international environmental issue, and it is essential to stabilize and reduce the concentration of CO2 in the atmosphere. While carbon capture and storage (CCS) can be used to help reduce atmospheric CO2 concentrations, another attractive and promising option is the carbon capture and utilization (CCU) strategy, in which the captured CO2 can be used as a renewable resource to produce high value-added chemicals. Significant progress has been made in recent years in the production of fuel-related C1 products such as CO, CH4, CH3OH, etc. from the hydrogenation of CO2. Among these products, the CO product is the most attractive because it can be used as a key chemical feedstock for the production of various hydrocarbons and oxygenates through Fischer-Tropsch synthesis (FT) or other syngas processes. It is ideal to selectively hydrogenate CO2 to CO through the reverse water gas shift reaction (RWGS) using hydrogen produced from renewable energy such as wind or solar energy. The reaction equation is: CO2+H2→CO+H2O, ΔH 0 298 = +41 kJ mol -1 .
[0003] In addition, understanding the reaction mechanism of the catalyst surface microstructure at the atomic level is of great significance for the rational design of RWGS catalysts with high activity and stability. As an acidic gas, CO2 has good thermodynamic stability and chemical inertness. The C=O bond in the CO2 molecule is very stable, and electrons need to be input to achieve the activation of the inert CO2. Therefore, it is urgent to develop good CO2 adsorption, easy activation and sufficient molecular transfer to promote the subsequent CO2 hydrogenation process for RWGS reactions. In this case, metal / solid base hybrid catalysts, such as MgO-based catalysts, have abundant basic sites, such as coordinated unsaturated oxygen sites (O nc ,n=3,4,5), defect sites and alkaline metal-oxygen ion pair sites to adsorb and activate CO2 gas. As an alkali metal oxide catalyst, MgO can effectively adsorb CO2 and activate it into carbonate species. It is very important to develop MgO-based catalysts with high activity, high selectivity and good stability. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a monodisperse Ce atom-modified MgO alkaline catalyst. The prepared alkaline catalyst has strong sintering resistance, high activity, good selectivity, strong stability, and exhibits good catalytic performance in the carbon dioxide hydrogenation reaction.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] In one aspect, the present invention provides a method for preparing a rare earth metal-modified MgO alkaline catalyst, the method comprising the following steps:
[0007] (1) completely dissolving cerium nitrate, magnesium nitrate hexahydrate and anhydrous citric acid in deionized water in a certain proportion to form a precursor solution;
[0008] (2) heating and stirring the precursor solution prepared in step (1) under vigorous stirring until the solution presents a gel state;
[0009] (3) drying the gel-like substance obtained in step (2) in an oven at 160-180° C. for 6-18 hours;
[0010] (4) Grinding the dry solid substance obtained in (3) into powder, and calcining in air at 450-800° C. for 1-4 h to obtain a Ce atom-modified MgO alkaline catalyst.
[0011] Based on the above technical solution, preferably, in the above step 1), the cerium nitrate precursor is selected from one of the following compounds: cerium nitrate hexahydrate, ammonium cerium nitrate, cerous nitrate hexahydrate.
[0012] Based on the above technical solution, preferably, in step 2), water is evaporated in a rotary evaporator, the heating is water bath heating, the water bath temperature is 40-80° C., the vacuum degree of the rotary evaporator is 40-90 mbar, and the rotary evaporation time is 1-4 h.
[0013] Based on the above technical solution, preferably, in step 4), the temperature is programmed in the muffle furnace at a rate of 1 to 10°C / min, the maximum calcination temperature is 450-800°C, and the retention time at the maximum temperature is 1 to 6 hours. The catalyst prepared at different calcination temperatures will affect the pore structure of the catalyst and the uniformity of the dispersion of rare earth atoms. The most preferred temperature is 600-700°C.
[0014] Based on the above technical solution, preferably, in step 1), the molar ratio of anhydrous citric acid to cerium nitrate and magnesium nitrate hexahydrate is: citric acid / metal atom = 0.5-3; the metal atom is the sum of Ce and Mg.
[0015] Another aspect of the present invention provides a rare earth metal-assisted modified MgO alkaline catalyst for carbon dioxide hydrogenation reaction synthesized by the above method.
[0016] Furthermore, in the above technical solution, Ce atoms are dispersed on MgO in a single-atom manner.
[0017] In addition, the present invention also provides a method for preparing carbon monoxide by hydrogenation of carbon dioxide, which comprises pressing a solid oxide particle catalyst into a reactor, and introducing a mixture of carbon dioxide and hydrogen into the reactor after reduction treatment to react and prepare a carbon monoxide product. In view of the good thermodynamic stability and chemical inertness of CO2, the present invention uses MgO material as an alkaline catalyst, and rare earth elements are modified to efficiently catalyze and hydrogenate carbon dioxide to generate product carbon monoxide. The catalyst has abundant raw materials, is green and economical, and has high carbon dioxide hydrogenation reaction activity, selectivity and stability.
[0018] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 a is a transmission electron microscope image of nano-MgO prepared in Example 1, Figure 1 b, c, d, and e are Ce atom-modified nano-MgO alkaline catalysts prepared in Examples 2, 3, 4, and 5, respectively. Figure 1 f is the transmission electron microscopy image of commercial MgO-C in Comparative Example 1.
[0020] Figure 2 This is a scanning transmission-high-angle annular dark field image of the Ce atom-modified nano-MgO alkaline catalyst prepared in Example 4.
[0021] Figure 3 Figure a, b, and d are the quasi-in-situ X-ray electron spectrum O1s spectrum, Mg1s spectrum, and electron paramagnetic resonance spectrum of the nano-MgO prepared in Example 1, the Ce atom-modified nano-MgO alkaline catalyst prepared in Example 4, and the commercial MgO-C in Comparative Example 1, respectively; Figure c is the UV-visible spectrum of the nano-MgO prepared in Example 1, the Ce atom-modified nano-MgO alkaline catalyst prepared in Examples 2, 3, 4, 5, and the commercial MgO-C in Comparative Example 1, respectively.
[0022] Figure 4 This is a graph showing the carbon dioxide hydrogenation reaction performance of the nano-MgO prepared in Example 1, the Ce atom-modified nano-MgO alkaline catalyst prepared in Examples 2, 3, 4, and 5, and the commercial MgO-C in Comparative Example 1. DETAILED DESCRIPTION
[0023] The specific implementation method of the present invention is described in detail below. The specific implementation method described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0024] Example 1
[0025] This preparation example is used to illustrate the alkaline catalyst based on modified nano-MgO and its preparation method provided by the present invention. The catalyst prepared in this example is MgO-D.
[0026] Dissolve 6.41g Mg(NO3)2·6H2O and 10.51g anhydrous citric acid in 20mL deionized water, stir thoroughly at room temperature for 3h, and place the obtained precursor solution in a rotary evaporator at a water bath temperature of 60℃ and a vacuum degree of 80mbar for rotary evaporation until the solution is in a gel state. The obtained gel material is placed in a 120℃ oven for drying for 12h, and then the obtained solid material is placed in a muffle furnace for roasting at 650℃ for 2h and a heating rate of 5℃ / min. When the temperature of the muffle furnace drops to room temperature, take out the sample and grind it into powder to obtain the catalyst solid oxide form.
[0027] Example 2
[0028] This preparation example is used to illustrate the alkaline catalyst based on modified nano-MgO and its preparation method provided by the present invention. The catalyst prepared in this example is Ce-MgO-D (0.4).
[0029] 0.01g Ce(NO3)2·6H2O, 6.37g Mg(NO3)2·6H2O and 10.47g anhydrous citric acid were dissolved in 20mL deionized water and stirred for 3h at room temperature. The obtained precursor solution was placed in a rotary evaporator at a water bath temperature of 60℃ and a vacuum degree of 80mbar for rotary evaporation until the solution was in a gel state. The obtained gel material was placed in a 120℃ oven for drying for 12h, and then the obtained solid material was placed in a muffle furnace for roasting at 650℃ for 2h and a heating rate of 5℃ / min. When the temperature of the muffle furnace dropped to room temperature, the sample was taken out and ground into powder to obtain the catalyst solid oxide form.
[0030] Example 3
[0031] This preparation example is used to illustrate the alkaline catalyst based on modified nano-MgO and its preparation method provided by the present invention. The catalyst prepared in this example is Ce-MgO-D (0.8).
[0032] 0.03g Ce(NO3)2·6H2O, 6.35g Mg(NO3)2·6H2O and 10.44g anhydrous citric acid were dissolved in 20mL deionized water and stirred for 3h at room temperature. The obtained precursor solution was placed in a rotary evaporator and rotary evaporated at a water bath temperature of 60℃ and a vacuum degree of 80mbar until the solution was in a gel state. The obtained gel material was placed in a 120℃ oven and dried for 12h. After that, the obtained solid material was placed in a muffle furnace for roasting. The roasting conditions were 650℃, 2h, and the heating rate was 5℃ / min. When the temperature of the muffle furnace dropped to room temperature, the sample was taken out and ground into powder to obtain the catalyst solid oxide form.
[0033] Example 4
[0034] This preparation example is used to illustrate the alkaline catalyst based on modified nano-MgO and its preparation method provided by the present invention. The catalyst prepared in this example is Ce-MgO-D (1.6).
[0035] Dissolve 0.05g Ce(NO3)2·6H2O, 6.40g Mg(NO3)2·6H2O and 10.49g anhydrous citric acid in 20mL deionized water, stir thoroughly at room temperature for 3h, place the obtained precursor solution in a rotary evaporator at a water bath temperature of 60℃ and a vacuum degree of 80mbar for rotary evaporation until the solution is in a gel state, place the obtained gel material in a 120℃ oven to dry for 12h, and then place the obtained solid material in a muffle furnace for roasting at 650℃, 2h, and a heating rate of 5℃ / min. When the temperature of the muffle furnace drops to room temperature, take out the sample and grind it into powder to obtain the catalyst solid oxide form.
[0036] Example 5
[0037] This preparation example is used to illustrate the alkaline catalyst based on modified nano-MgO and its preparation method provided by the present invention. The catalyst prepared in this example is Ce-MgO-D (4).
[0038] 0.13g Ce(NO3)2·6H2O, 6.09g Mg(NO3)2·6H2O and 10.16g anhydrous citric acid were dissolved in 20mL deionized water and stirred for 3h at room temperature. The obtained precursor solution was placed in a rotary evaporator at a water bath temperature of 60℃ and a vacuum degree of 80mbar for rotary evaporation until the solution was in a gel state. The obtained gel material was placed in a 120℃ oven for drying for 12h, and then the obtained solid material was placed in a muffle furnace for roasting at 650℃ for 2h and a heating rate of 5℃ / min. When the temperature of the muffle furnace dropped to room temperature, the sample was taken out and ground into powder to obtain the catalyst solid oxide form.
[0039] Comparative Example 1
[0040] Commercial MgO, the catalyst of this comparative example is MgO-C. The commercial MgO was purchased from Shanghai McLean Biochemical Technology Co., Ltd., CAS: 1309-48-4.
[0041] Comparative Example 2
[0042] Synthesis of CuZnAl catalyst. The catalyst was prepared by urea homogeneous precipitation method. 2.24g Cu(NO3)2·3H2O, 0.93g Zn(NO3)2·6H2O, 0.44g Al(NO3)3·6H2O, and 12.01g urea were dissolved in 100mL deionized water, stirred in a 95℃ water bath for 2h, aged at 95℃ for 24h, filtered, and washed with deionized water three times. Finally, dried in an oven at 60℃ for 12h, and then calcined in static air at 350℃ for 3h to obtain CuZnAl catalyst.
[0043] The morphology of the Ce-modified MgO alkaline catalyst synthesized by the present invention is observed using a transmission electron microscope and a scanning transmission electron microscope, and the degree of sample defects is analyzed by X-ray electron spectroscopy (XPS), ultraviolet visible light spectrum and EPR.
[0044] The transmission electron microscope (TEM) images of the alkaline catalysts with different Ce contents in Examples 1-6 and Comparative Example 1 are as follows: Figure 1 As shown, the catalyst surface morphology of Example 1 is irregular in shape, showing a rough surface edge structure. It is also found that the surface of the magnesium oxide of Examples 2-5 with added cerium becomes rougher than that of the magnesium oxide of Example 1 and Comparative Example 1 without cerium, with a large number of stepped step site structures and increased surface defects. At the same time, we found through scanning transmission microscopy-high angle annular dark field imaging (ATEM-HAADF) that the Ce atoms in the sample of Example 4 are dispersed on the surface of MgO (100) in the form of single atoms, and no clusters or nanoparticles of Ce are detected ( Figure 2 The increase in the number of MgO step structures in the samples of Example 2-5 with the addition of cerium is due to the fact that Ce atoms replace Mg atoms in MgO to reach their most thermodynamically favorable position. X-ray electron spectroscopy O1s spectrum, UV-visible spectrum and electron paramagnetic resonance spectrum show that the catalyst contains a large number of oxygen defects and oxygen vacancies ( Figure 3 ).
[0045] Example 6
[0046] This example is used to illustrate the method for hydrogenation of carbon dioxide provided by the present invention.
[0047] The metal oxides prepared in the above Examples 1-5 and the sample of Comparative Example 1 were tableted and loaded into a reactor. After reduction treatment, carbon dioxide and hydrogen were introduced for reaction. The loading amount of the catalyst was 100 mg, and the total flow rate of the reaction gas was 40 mL / min. The CO2 concentration in the raw gas was 24%, the H2 concentration was 72%, and N2 was the balance gas. The conditions of the carbon dioxide hydrogenation reaction and the results obtained are shown in Table 1.
[0048] CO2 conversion (%), CO selectivity (%) and CO2 reaction rate (mmol g -1 cat. s -1 ) is calculated as follows:
[0049]
[0050] Table 1. Test results of the catalysts prepared in Examples 1-6 and Comparative Example 1 for catalytic hydrogenation of CO2 to CO at a reaction temperature of 600°C
[0051]
Claims
1. A method for synthesizing a modified nano-MgO alkaline catalyst, characterized in that: The following steps are involved: (1) completely dissolving cerium nitrate, magnesium nitrate hexahydrate and anhydrous citric acid in deionized water in a certain proportion to form a precursor solution; (2) heating and stirring the precursor solution prepared in step (1) under vigorous stirring until the solution presents a gel state; (3) drying the gel-like substance obtained in step (2) in an oven at 160-180° C. for 6-18 hours; (4) Grinding the dry solid material obtained in (3) into powder, and calcining in air at 450-800° C. for 1-4 h to obtain a Ce atom-modified MgO alkaline catalyst.
2. The method for synthesizing the modified nano-MgO alkaline catalyst according to claim 1, characterized in that: In step 1), the cerium nitrate precursor is selected from one of the following compounds: cerium nitrate hexahydrate, ammonium cerium nitrate, cerous nitrate hexahydrate.
3. The method for synthesizing the modified nano-MgO alkaline catalyst according to claim 1, characterized in that: In step 2), the precursor solution is evaporated in a rotary evaporator, the heating is water bath heating, the water bath temperature is 40-80° C., the vacuum degree of the rotary evaporator is 40-90 mbar, and the rotary evaporation time is 1-4 h.
4. The method for synthesizing the modified nano-MgO alkaline catalyst according to claim 1, characterized in that: In step 4), the temperature is programmed in a muffle furnace at a rate of 1 to 10° C. / min, the highest calcination temperature is 450 to 800° C., and the retention time at the highest temperature is 1 to 6 hours.
5. The method for synthesizing the modified nano-MgO alkaline catalyst according to claim 1, characterized in that: In step 1), the molar ratio of anhydrous citric acid to cerium nitrate and magnesium nitrate hexahydrate is: citric acid / metal atom=0.5-3; the metal atom is the sum of Ce and Mg.
6. A modified nano-MgO alkaline catalyst synthesized by the synthesis method according to any one of claims 1 to 4.
7. The modified nano-MgO alkaline catalyst according to claim 5, characterized in that: Ce atoms are dispersed on MgO in a single-atom manner.
8. Use of the modified nano-MgO alkaline catalyst as claimed in claim 5 or 6 in the reaction of preparing carbon monoxide by hydrogenation of carbon dioxide.
9. The use according to claim 8, characterized in that The solid oxide particle catalyst is pressed into tablets and loaded into a reactor. After reduction treatment, a mixture of carbon dioxide and hydrogen is introduced to react and prepare a carbon monoxide product.
Citation Information
Patent Citations
Ce-K co-doped MgO-based medium-temperature CO2 adsorption material and preparation method thereof
CN113304722A
Polyethylene resin compostion with excellent gloss and pipe prepared using the same
KR1020230069640A
Polysilsesquioxane particle having both UV-C and UV-B absorption properties and preparation method thereof
KR102727455B1